The unbudgeable curmudgeon - Burgess, Matthew; Woodcock, Fiona (New York : Alfred A. Knopf, 2019)
"Have you ever seen a curmudgeon that looks like your brother, but is in such a bad mood you hardly recognize him? You can try all the peanut butter sandwiches and brownies you have, but he is not moving. Nothing works, especially nudging, and he just makes you so grumpy that eventually you have no choice but to fight back--and then... Have you ever become a curmudgeon that just won't budge?"--Amazon.
107108
Keywords: Brothers and sisters -- Juvenile fiction; Emotions; Anger; Picture books for children; Obstinacy; Picture books for children; Fiction; Juvenile works